(untitled) (Economic and Political Thought, 2014)
The article aims to discuss the international competitiveness of Greece in comparison with Germany, the Eurozone and the European Union as a whole in the context of Greece’s public debt crisis. The first part evokes the definition of international competitiveness that is quoted in literature. Taking into account the fact that competiveness cannot be presented as a single figure, the author analyses a series of macro-economic indicators connected with trade in goods and services and unit labour costs and he examines the level of inflation and unemployment as well as the share of public debt and budget balance in the GDP of selected countries of the Eurozone and the European Union. In addition, the position of Greece and Germany in the international competitiveness rankings and the GDP growth indicators are presented. The analysed data show that the international position of Greek economy is much lower than that of Germany. As it could have been expected, the situation was worsened by the global economic crisis of 2008, which demonstrated the weakness of Greece while it only upset the internal balance in Germany. Despite Germany’s problems with maintaining public debt and budget deficit in relation to the GDP at the level specified by the Stability and Growth Pact, these did not have a bad impact on the balance of current turnover and a drastic increase in the unemployment level in the country. The competitive position of Germany measured by various competitiveness rankings did not change either and is much better than Greece’s.